A Narrative Review on Prevention and Treatment Strategies of Post Spinal Anesthesia Headache - Ali Jabbari; Shabnam Tabasi; Nadia Bani Hashem; Alireza Jahangirifard (Archives of Anesthesia and Critical Care, 2021)
Background: Post spinal anesthesia headache (PSAH) is a headache occurring after spinal anesthesia induction due to Dura and arachnoid puncture and has a significant effect on the patients’ post operative well being. Methods: We run a cross sectional descriptive study on patient under spinal anesthesia that suffer from post spinal anesthesia headache parallel with a review on observational and experimental studies in the medical databases of PubMed, Scopus, Embase, Cochrane for preparing a strategy in prevention and treatment of post spinal anesthesia headache. Aim of this study was adapting different treatment method and prevention system of Post Spinal Anesthesia Headache (PSAH) according to our facilities base on our observation and experiences. Results: The overall incidence of post-Spinal Anesthesia headache has a very wide range. Its incidence obtained 17.3% by spinal needle 25G Quincke in our observation. Under hydration and tension headaches could be a factor influencing the incidence of PSAH. Intravenous administration of caffeine may be effective for prophylaxis of PSAH. Pregabalin has also been shown to alleviate PSAH. Drugs that have been used to treat PSAH include caffeine, NSAIDs, vasopressin, hydrocortisone, dexamethasone, theophylline, sumatriptan, gabapentin and adrenocorticotropic hormone (ACTH). Conclusion: A combination of keeping patients normovulemic during the spinal anesthesia induction and prophylaxis prescription of caffeine and Dexamethone before and; Aminophylline and NSAIDS after the procedure could have a main role in keeping and treatment of the patient from PSAH.